Investigation of ejector re-compression absorption refrigeration cycle - Wu, Shenyi (1999)
This thesis describes a theoretical and experimental investigation of the ejector re-compression lithium bromide absorption refrigeration cycle. In this novel cycle, a steam ejector is used to enhance the concentration process by compressing the vapour to a state that it can be used to re-heat the solution from where it was evolved. Since this cycle recovers the heat otherwise wasted in a conventional absorption cycle, the energy performance of the cycle is improved. The theoretical study shows that the improvement of the efficiency is proportional to the performance of the steam ejector. A COP of 1.013 was achieved from the experiment in this investigation.